Pelatihan Pembuatan Cinderamata dari Kain Flannel kepada Anak Asuh di LKSA Muhammadiyah Selong - Nova Hari Santhi; Ratna Yuniarti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2022)
The purpose of this activity is to empower LKSA foster children including: The formation of new entrepreneurs, providing life skills for foster children in the form of; training on making accessories and souvenirs for teenagers, adults and children such as gallon lids, key chains, room decorations, tissue holders, brooches, room displays, dolls, pillows and making piggy banks, souvenirs for graduation and others from flannel . The method used to solve the problems faced by partners is by conducting training in making various souvenirs using flannel. The implementation of training activities to make souvenirs from flannel for foster children at the Selong Muhammadiyah orphanage has been carried out well. Students make products in the form of tissue boxes, cell phones, pencil cases, brooches, hair tie clips, and key chains. Starting from preparation (selection of materials, measurements, preparation of tools), the use of correct equipment, the accuracy of the steps to make souvenirs, the suitability of the final results presented according to the expected criteria, arranging equipment after completion of activities, creativity of functional object products, neatness of functional objects, combinations functional object color. Overall the results in this community service activity are training to make souvenirs from flannel in the form of tissue holders, cellphone holders, pencil cases, brooches, hair clips / hair ties, and key chains in very good categories, besides that this activity can also provide skills to younger siblings and able to develop these talents in the future. Student response to the implementation of this training activity was very good. This can be seen from the student attendance indicator reaching 100% of the target, and during the activity they were very enthusiastic about participating in the activity from the beginning to the end of the activity.